Progress in Topical and Transdermal Drug Delivery Research—Focus on Nanoformulations - Lunter, Dominique; Klang, Victoria; Eichner, Adina; Savic, Sanela M.; Savic, Snezana; Lian, Guoping; Erdő, Franciska (Pharmaceutics, 2024)
Skin is the largest organ and a multifunctional interface between the body and its environment. It acts as a barrier against cold, heat, injuries, infections, chemicals, radiations or other exogeneous factors, and it is also known as the mirror of the soul. The skin is involved in body temperature regulation by the storage of fat and water. It is an interesting tissue in regard to the local and transdermal application of active ingredients for prevention or treatment of pathological conditions. Topical and transdermal delivery is an emerging route of drug and cosmetic administration. It is beneficial for avoiding side effects and rapid metabolism. Many pharmaceutical, technological and cosmetic innovations have been described and patented recently in the field. In this review, the main features of skin morphology and physiology are presented and are being followed by the description of classical and novel nanoparticulate dermal and transdermal drug formulations. The biophysical aspects of the penetration of drugs and cosmetics into or across the dermal barrier and their investigation in diffusion chambers, skin-on-a-chip devices, high-throughput measuring systems or with advanced analytical techniques are also shown. The current knowledge about mathematical modeling of skin penetration and the future perspectives are briefly discussed in the end, all also involving nanoparticulated systems.